Pro-poor tourism: a new tourism policy in China for poverty alleviation - YANG, Wei; Aimimtham, Sukanya; BI, Chuanchen (International Journal of Psychosocial Rehabilitation, 2020)
Poverty reduction is now a major issue for developing countries to focus on and whose success, or otherwise, will directly affect upon the achievement of development of the nation. China has made significant advances in poverty reduction since the launch of its reform and open policy in 1978, however, the poverty issue is still obviously present. The Central government of China launched a new strategic plan for poverty alleviation called ‘precision poverty alleviation’ in 2015. It is aimed at taking targeted measures for poverty alleviation. Moreover, most of the poverty regions overlap the famous tourism resources, which offer the best opportunity for the tourism industry to be involved in this new poverty alleviation strategy. This paper mainly focusses on pro-poor tourism as a new tourism policy for precision poverty alleviation. Specifically, this paper is divided into three themes based on the focus topic. The first theme overviews poverty alleviation in China, the processing period and the gap between the previous strategy and the poverty alleviation situation. The second theme describes the importance of pro-poor tourism for precision poverty alleviation, and explores the development model. The last theme offers academic discussion and future predictions related to this new tourism policy for precision poverty alleviation in China.